KAJIAN KEMUNDURAN MUTU IKAN JELAWAT (Leptobarbus hoevenii) SEGAR DENGAN PERENDAMAN DALAM LARUTAN KITOSAN - Alparis, Ahmad; ', Edison; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThis research was intended to evaluate the deterioration of fresh mad barb (Leptobarbus hoevenii) with soaking in chitosan solution. The method used in this study was the experimental method, with concentration of chitosan solution was 0%; 0.1%; 0.3% and 0.5%. The fresh mad barb (Leptobarbus hoevenii) was evaluated for organoleptic tested; including eye visually, gills, mucous, meat (color and visually), odor and texture; total plate count and total volatile base.The highest concentration of chitosan solution could increased the fish quality of fresh mad barb (Leptobarbus hoevenii). The concentration with 0,5% of chitosan solution was the best treatment; could defend the fish quality on eye parameter for 15 h with value 7.08; gills 12 h (6.72), mucous 15 h (7.00); meat 15 h (7.11); odor 21 h (7.04); texture 15 h (7.12); total plate count 12 h (4.04x105 colony/gram) and total volatile base 21 h (33.07 mg/100 gram).Keywords: mad barb (Leptobarbus hoevenii), fresh fish, chitosan, deterioration